P70 SEVERE DUMPING SYMPTOMS ARE UNCOMMON FOLLOWING TRANSTHORACIC ESOPHAGECTOMY BUT SIGNIFICANTLY DECREASE HEALTH-RELATED QUALITY OF LIFE IN LONG-TERM, DISEASE FREE SURVIVORS. (23rd November 2019) - Klevebro, F; Boshier, P R; Savva, K V; Waller, A; Hage, L; Hanna, G B; Low, D
Abstract: Aim: The aim of the study was to increase the knowledge about dumping symptoms after esophagectomy and the association to health-related quality of life. Background and Methods: High quality documentation of dumping symptoms after esophagectomy is currently limited. The aim of the study was to describe the incidence of symptoms associated with dumping syndrome and their relationship with health-related quality of life after esophagectomy. The study cohort was identified from prospective IRB-approved databases from two high volume esophagectomy centers. Patients that were alive and without evidence of recurrence in April 2018 completed the validated Dumping Symptom Rating Scale and health-related quality of life questionnaires. Compound dumping symptom score was created by combining the individual scores for severity and frequency for each symptom. Results: In total, 171 patients who underwent esophagectomy 1995-2017 responded to the questionnaires, corresponding to a response rate of 77.0%. Median age was 66 years and median time from operation to survey was 5.5 years. Absent or mild problems in all nine dumping symptoms were reported by 94 (59.5%) patients, 19 (12.0%) patients reported moderate or severe problems in at least three symptoms, the most common being "a need to lie down, " "diarrhea, " and "stomach cramps." Increasing compound dumping symptom score was associated with significantly decreased function scores in all aspects of health-related quality of life except physical functioning (P<0.005). Conclusions: Esophagectomy has the potential to change long-term eating patterns, however the majority of patients in the study did not have severe postoperative dumping symptoms. On the other hand moderate to severe dumping symptoms, which were reported by 12% of patients in this study were strongly associated with decreased health-related quality of life.